High-Resolution Structures of Large Ribosomal Subunits from Mesophilic Eubacteria and Halophilic Archaea at Various Functional States - Yonath, A. (Current Protein and Peptide Science, 2002)
Structural analysis of the recently determined high resolution structures of the small and the large ribosomal subunits from three bacterial sources, assisted by the medium resolution structure of a complex of the entire ribosome with three tRNAs, led to a quantum jump in our understanding of the process of the translation of the genetic code into proteins. Results of these studies highlighted dynamic aspects of protein biosynthesis illuminated the modes of action of several antibiotics indicated strategies adopted by ribosomes for maximizing their functional activity and revealed a wealth of architectural elements, including long tails of proteins penetrating the particle's cores and stabilizing the intricate folds of the RNA chains. Binding of substrate analogues showed that the decoding and the peptide-bond formation are accomplished mainly by RNA. However, several proteins may be functionally relevant in directing the mRNA and in mediating the proper orientation of the tRNA molecules within the ribosomal rRNA frame. Elements involved in intersubunit contacts or in substrate binding are inherently flexible, but maintain well-ordered characteristic conformations in unbound particles. The ribosomes utilize this conformational variability for optimizing their efficiency and minimizing non-productive interactions, hence disorder of functionally relevant features may be linked to less active conformations or to far from physiological conditions. Clinically relevant antibiotics bind almost exclusively to rRNA. In the small subunit they affect the decoding accuracy or limit conformational mobility and in the large subunit they either interfere with substrate binding, by interacting with components of the peptidyl transferase cavity, or hinder the progression of the growing peptide chain.
Keywords: Mesophilic Eubacteria